THE EFFECT OF ROUND TABLE TECHNIQUE ON THE WRITING ABILITY OF THE SECOND YEAR STUDENTS OF SMPN 40 PEKANBARU IN WRITING RECOUNT TEXTS - Simanjuntak, Hari Saputra; Delfi, Syofia; Afrianto, Afrianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This pre-experimental research is aimed to find out whether or not there is an effect of Round Table Technique on the writing ability of the second year students of SMPN 40 Pekanbaru in writing recount texts. This research used one group pre-test and post-test design. In conducting this research, a single group from the second grade was selected to be a sample by using Cluster Random Sampling. There are 36 students as the sample. The results of this study shows that the mean score of post-test was higher than pre-test (49.12 > 41.13). After analyzing the data, the writer found that t-test score was -10.645 while t-table score in significance level 5% df = 35 was 2.030. Since the value of the t-test was higher than the t-table, it can be concluded that alternative hypothesis was accepted. It means that “there is an effect of Round Table Technique on the students’ writing ability of SMPN 40 Pekanbaru in writing recount texts. Based on the research findings, it is suggested that Round Table Technique can help the students improve their writing ability especially in writing recount texts.Key Words: Effect, Round Table Technique, Writing Ability, Recount Text